Pengaruh Media Pembelajaran Terhadap Kemampuan Menyimak Bahasa Inggris - Unpris Yastanti (Wanastra: Jurnal Bahasa dan Sastra, 2015)
The objective of this research is to know the effects of of learning media towards student’s listening skill. The research methodology that is used eksperimen methodology. The subject of this research is taken from the whole population students of at Private Universities in Jakarta and sampel is taken from fourth term. From this research shown that the result of SPSS Fo=105,959 and sig=0,000(0,000<0,05), it can be concluded that the learning media give significant effect towards student’s listening skill.